Professional competences of radio and television workers: correlation of students’ learning and cognitive activities with production conditions and requirements - Davydik, Alexander S.; Mintsevich, Darya A. (University Pedagogical Journal, 2024)
The article describes the requirements of the labour market to the radio and television workers. The results of the ascertaining research on the assessment of students’ preferences within the framework of educational activity and its correlation with the labour market are presented. The preliminary settings for mastering professional competences are demonstrated. The initial motivation of students and deviations in its implementation are characterised. The problems of application and development of professional skills and abilities in the conditions of real production are described.